Differential effects of acellular embryonic matrices on pluripotent stem cell expansion and neural differentiation. (December 2015) - Yan, Yuanwei; Martin, Lauren M.; Bosco, Dale B.; Bundy, Joseph L.; Nowakowski, Richard S.; Sang, Qing-Xiang Amy; Li, Yan
Abstract: Extracellular matrices (ECM) derived from pluripotent stem cells (PSCs) provide a unique tissue microenvironment that can direct cellular differentiation and tissue regeneration, and rejuvenate aged progenitor cells. The unlimited growth capacity of PSCs allows for the scalable generation of PSC-secreted ECMs. Therefore, the derivation and characterization of PSC-derived ECMs is of critical importance in drug screening, disease modeling and tissue regeneration. In this study, 3-D ECMs were generated from decellularized undifferentiated embryonic stem cell (ESC) aggregates (AGG), spontaneously differentiated embryoid bodies (EB), and ESC-derived neural progenitor cell (NPC) aggregates. The capacities of different ECMs to direct proliferation and neural differentiation of the reseeded mouse ESCs and human induced pluripotent stem cells (iPSCs) were characterized. Proteomic analysis by liquid chromatography–tandem mass spectrometry (LC-MS/MS) revealed protein expression profiles that reflected distinct niche properties for each tested ECM group. The reseeded mouse ESCs and human iPSCs responded to different types of ECMs with different cellular phenotypes. Cells grown on the AGG-ECM displayed high levels of pluripotent markers Oct-4 and Nanog, while the cells grown on the NPC-ECM showed increased expression of neural marker β-tubulin III. The expression levels of β-catenin were high for cells grown on the AGG-ECM and the EB-ECM, but reduced in cells grown on the NPC-ECM, indicating a possible role of Wnt/β-catenin signaling in the cell-matrix interactions. This study demonstrates that PSC-derived ECMs can influence stem cell fate decisions by providing a spectrum of stem cell niche microenvironments during tissue development.